Revision of type specimens of Astaena (Coleoptera: Scarabaeidae: Melolonthinae: Sericini) described by L.W. Saylor - Pacheco, Thaynara L.; Monné, Marcela L.; Vaz-De-Mello, Fernando Z.; Ahrens, Dirk (European Journal of Taxonomy, 2021)
This is the first part of a revision of the type specimens of the South American Sericini. Herein, we examine type specimens of Astaena described by Lawrence Webster Saylor (1913–1999). We provide diagnostic redescriptions, images of habitus, aedeagus, and labels of the type specimens of all 18 species described by him in the genus Astaena. We raise Sayloria Frey, 1973, a former subgenus of Symmela Erichson, 1835 that includes three species, to genus level. Our study results in the following new combinations and synonymy: Sayloria bicoloripes (Saylor, 1946) comb. nov. (= A. postnodata Frey, 1973 syn. nov.), S. abcora (Saylor, 1946) comb. nov. (= A. apolinarmaria Saylor, 1946 syn. nov.) and S. pottsi (Saylor, 1946) comb. nov.